The production and properties of Al3Ti reinforced functionally graded aluminum matrix composites produced by the centrifugal casting method - Savas, Omer (IOP Publishing Ltd, 2019)
In this study, the production and properties of titanium tri-aluminide (Al3Ti) particle reinforced functionally graded composites (FGCs) by a centrifugal casting method, are investigated. FGCs were produced by using Al-Ti master alloy which was alloyed with copper and silicon and without alloying to obtain three types of composites, namely Al3Ti/Al, Al3Ti/Al-Si and Al3Ti/Al-Cu FGC. It was observed that produced composites contain two different area: the functionally graded and Al3Ti-free area. The ratio and size of Al3Ti particles were found to change regionally in functionally graded area of each composite type. The effects of the regional change in functionally graded area and both the reinforcement ratio and particle size of composite types were discussed using statistical techniques. In addition, density, Brinell hardness and abrasive wear property of Al3Ti particle reinforced FGCs have been examined inwardly from the outer surface of composites depending on the centrifugal force direction. The results showed an improvement in Brinell hardness value inwardly from the outer surface of composites in each composite type. It was observed that the volumetric wear loss of composites were reduced by increasing the ratio of Al3Ti particles in the matrix.
Keywords: Al composites; functionally graded materials; In situ Al3Ti; wear; MECHANICAL-PROPERTIES; WEAR BEHAVIOR; FABRICATION; ALLOY; MICROSTRUCTURES; PARTICLE; Materials Science